Computer‐predicted peptides that mimic discontinuous epitopes on the A2 domain of factor VIII. (24th November 2014) - Lebreton, A.; Simon, N.; Moreau, V.; Demolombe, V.; Cayzac, C.; Nguyen, C.; Schved, J.‐F.; Granier, C.; Lavigne‐Lissalde, G.
Summary Development of antibodies (Abs) against factor VIII (FVIII) is a severe complication of haemophilia A treatment. Recent publications suggest that domain specificity of anti‐FVIII antibodies, particularly during immune tolerance induction (ITI), might be related to the outcome of the treatment. Obtaining suitable tools for a fine mapping of discontinuous epitopes could thus be helpful. The aim of this study was to map discontinuous epitopes on FVIII A2 domain using a new epitope prediction functionality of the PEPOP bioinformatics tool and a peptide inhibition assay based on the Luminex technology. We predicted, selected and synthesized 40 peptides mimicking discontinuous epitopes on the A2 domain of FVIII. A new inhibition assays using Luminex technology was performed to identify peptides able to inhibit the binding of anti‐A2 Abs to A2 domain. We identified two peptides (IFKKLYHVWTKEVG and LYSRRLPKGVKHFD) able to block the binding of anti‐A2 allo‐antibodies to this domain. The three‐dimensional representation of these two peptides on the A2 domain revealed that they are localized on a limited region of A2. We also confirmed that residues 484–508 of the A2 domain define an antigenic site. We suggest that dissection of the antibody response during ITI using synthetic peptide epitopes could provide important information for the management of patients with inhibitors.